(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2015)
The aim of this article is to discuss the impact of funding from The Rural Development Programme for 2007-2013 on the functioning of chosen indyvidual agricultural holding. In the area of The Rural Development Programme for 2007-2013 the studied agricultural holding benefited from the three measures of axis 1: setting-up of youngfarmers, early retirement and modernisation of agricultural holdings. Implemented measures influenced significantly to the development and functioning of the holding.